Information technology, revenue creation and growth: an international comparison of causality. (9th March 2007) - Ma, Jianyu; Soydemir, Gokce
In this paper, we examine the extent of the relationship between PC installation and revenue creation using Gross Domestic Product (GDP) growth in different economies and by running a series of Granger causality tests. Our findings show that in developed economies the total PC installation and the PC installation in home market Granger cause GDP growth, whereas GDP growth only Granger causes the PC installation in the market for education. However, in developing economies, there appears to be a unidirectional causality in that GDP growth Granger causes total PC installation, PC installation in education and PC installation in business and government markets. We do not find any PC installation variables Granger causing GDP growth, including PC installation in home market. Overall, our results show that developing economies, unlike developed economies, do not gain from investing in Information Technology (IT) in the short run.